Extra precision docking, free energy calculation and molecular dynamics studies on glutamic acid derivatives as MurD inhibitors. (August 2017) - Azam, Mohammed Afzal; Jupudi, Srikanth
Graphical abstract: Highlights: Putative binding modes of thirty MurD inhibitors was investigated. Docking, MM-GBSA and 10 ns dynamics simulation are used for this purpose. Van der Waals term is the driving force for ligands binding. MD and ΔGbind results of most potent inhibitor displayed stable and favorable binding. Abstract: The binding modes of well known MurD inhibitors have been studied using molecular docking and molecular dynamics (MD) simulations. The docking results of inhibitors1-30 revealed similar mode of interaction with Escherichia coli -MurD. Further, residues Thr36, Arg37, His183, Lys319, Lys348, Thr321, Ser415 and Phe422 are found to be important for inhibitors and E. coli -MurD interactions. Our docking procedure precisely predicted crystallographic bound inhibitor7 as evident from root mean square deviation (0.96 Å). In addition inhibitors2 and3 have been successfully cross-docked within the MurD active site, which was pre-organized for the inhibitor7 . Induced fit best docked poses of2, 3, 7 and15 /2Y1O complexes were subjected to 10 ns MD simulations to determine the stability of the predicted binding conformations. Induce fit derived docked complexes were found to be in a state of near equilibrium as evident by the low root mean square deviations between the starting complex structure and the energy minimized final average MD complex structures. The results of molecular docking and MD simulations described in this study will be useful for the development of new MurD inhibitors with high potency.